If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 3(5x + 8) = 0 Reorder the terms: 2x + 3(8 + 5x) = 0 2x + (8 * 3 + 5x * 3) = 0 2x + (24 + 15x) = 0 Reorder the terms: 24 + 2x + 15x = 0 Combine like terms: 2x + 15x = 17x 24 + 17x = 0 Solving 24 + 17x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-24' to each side of the equation. 24 + -24 + 17x = 0 + -24 Combine like terms: 24 + -24 = 0 0 + 17x = 0 + -24 17x = 0 + -24 Combine like terms: 0 + -24 = -24 17x = -24 Divide each side by '17'. x = -1.411764706 Simplifying x = -1.411764706
| 2(x+3)-4=16 | | (-5+5w+2v)(-6)= | | 15x^5+6x^3=-20x^4-8x^2 | | 8x-(6x-2)=2 | | 18v-(8v-7)=67 | | 3/5w-7/3=-5/2 | | -2y+24=6 | | -4(n+2)=(n-4) | | 1/2×12 | | 10m^2-21m-6=0 | | 6(2x-5)=4(x+8) | | 25=x-(3x+5) | | X-1/3-2/3 | | x^2+y-10x+2y+17=0 | | f(-3)=-3+9 | | ×-1/3-2/3 | | 5-6p=-79 | | x^7+x^4-9x^3=9 | | (420)6/180= | | (420)6/180=x | | 25+4m+25+4m=159 | | X/28=2/10 | | 6(5x-3)=12 | | (3/5w)-(5/3)=(-7/4) | | 1-x=4+17 | | 5ab-3ab+ab= | | m-(5)-(-12m)= | | -3/10=-31/20*10/3u | | B/13=3/13 | | x/4=3/× | | x+x+0.05+x+0.05+1.06=8.75 | | (-2)*(6)= |